2017
DOI: 10.1038/leu.2017.135
|View full text |Cite
|
Sign up to set email alerts
|

A novel agent SL-401 induces anti-myeloma activity by targeting plasmacytoid dendritic cells, osteoclastogenesis and cancer stem-like cells

Abstract: Novel therapies for multiple myeloma (MM) can target mechanism(s) in the host-MM bone marrow (BM) microenvironment mediating MM progression and chemoresistance. Our studies showed increased numbers of tumor-promoting, immunosuppressive and drug-resistant plasmacytoid dendritic cells (pDCs) in the MM BM microenvironment. pDC-MM cell interactions upregulate interleukin-3 (IL-3), which stimulates both pDC survival and MM cell growth. Since IL-3 R is highly expressed on pDCs in the MM BM milieu, we here targeted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
(64 reference statements)
1
33
0
Order By: Relevance
“…We have previously shown that pDCs from MM patients have significantly impaired ability to induce T cell proliferation versus normal pDCs [3,4,[15][16][17]. In our studies, elevated expression of immune checkpoint PD-L1 and toll-like-receptor (TLR-9/TLR-7) negatively regulate pDCs immune function; conversely, both TLR9/TLR7 agonists and anti-PD-L1 Abs activate pDCs and restore the ability of pDCs to induce T cell proliferation [4,15,17].…”
Section: Inhibition Of Kmo Activates MM Pdcs and Increases T Cell Promentioning
confidence: 65%
See 1 more Smart Citation
“…We have previously shown that pDCs from MM patients have significantly impaired ability to induce T cell proliferation versus normal pDCs [3,4,[15][16][17]. In our studies, elevated expression of immune checkpoint PD-L1 and toll-like-receptor (TLR-9/TLR-7) negatively regulate pDCs immune function; conversely, both TLR9/TLR7 agonists and anti-PD-L1 Abs activate pDCs and restore the ability of pDCs to induce T cell proliferation [4,15,17].…”
Section: Inhibition Of Kmo Activates MM Pdcs and Increases T Cell Promentioning
confidence: 65%
“…To determine whether pharmacological inhibition of KMO alters pDC-mediated T and NK cell anti-MM immune responses in the MM-BM milieu, we next utilized our coculture models of host-MM tumor cells, pDCs, T cells, and NK cells. These coculture models of patient pDCs, T cells, or NK cells with autologous MM cells have been useful in validating immune checkpoint PD-L1 as therapeutic target, as well as supporting ongoing clinical trials of anti-PD-L1 Abs in MM [3,4,16,23,24]. Using these models, we next examined whether KMO blockade can trigger the generation of MMspecific pDC-induced cytotoxic T lymphocytes ex vivo.…”
Section: Kmo Blockade Triggers Pdc-induced T and Nk Cell-mediated Antmentioning
confidence: 99%
“…12,13 Importantly, extensive research has shown the role of plasmacytoid dendritic cells (DCs) in promoting MM cell survival and drug resistance, 14 providing the framework for targeting plasmacytoid DCs/MM cells interaction in novel therapies. 15,16 Similarly, increased expression of immune checkpoints, ie PD-1/PD-L1, in T cells and MM cells, promotes tumor immune evasion and has been also associated to progression from precursor stages. 13,17 Therapeutic targeting by means of immune checkpoint inhibitor in MM will be discussed later in this review.…”
Section: Immune Dysfunction In MMmentioning
confidence: 99%
“…Plasmacytoid dendritic cells from patients with MM exhibit increased numbers in the bone marrow compared with those in normal donors; moreover, pDCs are more frequently localized in MM bone marrow than in MM peripheral blood, representing a functional impairment ( 22 , 59 ). The interaction between pDCs (BDCA2) and MM cells (CD138) increases the production of cytokines and chemokines, which can not only prolong the survival of pDCs but also confer growth, survival, and drug resistance in MM cells ( 59 ). Finally, pDC-MM cells surface receptor-ligand interactions (BAFF/APRIL and RANK/RANKL) trigger MM cell growth/survival through the nuclear factor (NF)-ÎșB pathway.…”
Section: Pdcs In Tumor Microenvironmentsmentioning
confidence: 99%
“…In vitro and in vivo studies have revealed that IL-3 can prolong pDC survival ( 22 ). Ray et al recently demonstrated that SL-401, a novel anti-IL-3R antibody, blocks pDC-induced MM cell growth by targeting pDCs ( 59 ). These studies therefore validated the targeting of pDC-MM interactions as a therapeutic strategy to overcome drug resistance in MM.…”
Section: Pdcs In Tumor Microenvironmentsmentioning
confidence: 99%